Some aspects of the ownership and use of motor vehicles in South Africa - Welgemoed, P. J.(Peter Johannes) (Stellenbosch : Stellenbosch University, 2012)
Originally published in Afrikaans as the author's thesis (M. Comm. -- University of Stellenbosch).